2006
DOI: 10.1182/blood-2006-02-005827
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 deficiency by mature neutrophils has differential effects on L-selectin shedding

Abstract: L-selectin directs neutrophils to sites of inflammation, and upon their activation, surface expression of the receptor is rapidly down-regulated by ectodomain shedding. Tumor necrosis factor-␣-converting enzyme (TACE, or ADAM17) is a sheddase of L-selectin; however, Adam17 gene targeting (ADAM17 ⌬Zn/⌬Zn ) in mice is perinatal lethal and its role in L-selectin shedding by mature neutrophils has not been determined. This was addressed here by using radiation-chimeric mice reconstituted with ADAM17 ⌬Zn/⌬Zn fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 44 publications
9
120
0
Order By: Relevance
“…Here we demonstrate that ADAM17, which leads to cleavage of CD62L in lymphocytes and neutrophils, 21 also performs this function in NK cells. In murine models of inflammation or bone marrow transplantation, NK cells home to lymph nodes and other Figure 5.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Here we demonstrate that ADAM17, which leads to cleavage of CD62L in lymphocytes and neutrophils, 21 also performs this function in NK cells. In murine models of inflammation or bone marrow transplantation, NK cells home to lymph nodes and other Figure 5.…”
Section: Discussionmentioning
confidence: 65%
“…ADAM17 has been shown to mediate the shedding of CD62L, 21 as well as various other molecules. 31 Thus, we hypothesized that ADAM17 may be an important effector protease to regulate the surface density of CD16 and CD62L in NK cells.…”
Section: Adam17 Is Expressed On Nk Cells and Leads To Loss Of Cd16 Anmentioning
confidence: 99%
See 1 more Smart Citation
“…S2B). Because iRhom2 is required for the maturation and function of ADAM17 in myeloid cells, we isolated CD45 high leukocytes from the brain to assess the function of ADAM17 by measuring the phorbol ester (phorbol 12-myristate 13-acetate; PMA)-stimulated shedding of CD62L (L-selectin) (31). We found that the PMAstimulated down-regulation of CD62L was comparable in wild-type and iR1 −/− brain leukocytes ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…ADAM17 acts as a sheddase where it processes and thereby regulates a variety of mediators and receptors, including EGFR transactivation (14), ectodomain shedding of TNF-␣ and TNFI and TNFII (TNF receptors I and II, respectively) (32), platelet glycoproteins (33), neurotrophin receptors (34), L-selectin (35), angiotensin-converting enzyme-2 (36), and fractalkine (37). ADAM17 activity in pulmonary epithelial cells has been reported to be induced by IL-13 (19,30), and TACE/ADAM17 processing of EGFR ligands has been found to play a critical role in IL-13-induced airway responses and proliferation of epithelial cells (19,30).…”
Section: Volume 283 • Number 48 • November 28 2008mentioning
confidence: 99%